Die altnubischen Dörfer Bāb und Al-Ğūwānī. Zeugen einer versunkenen Kultur - Zabrana, Lilli (Holzhausen, 2019)
The presented volume aims to carry out a socio-cultural case study focusing on two abandoned Nubian villages in Upper Egypt, which are regarding their formation and abandonment closely connected with the construction of the British Dam south of Aswan and the following floods around 1900. Besides the documentation of architecture and associated find material, the special nature of the research strategy involved a close cooperation with the descendents of the village inhabitants and other Nubians still living in the sourroundings of the affected area.Through the interdisciplinary research strategy and the combination of a variety of methods in the fields of Archaeology, Building research and Social Anthropology, standard interpretations could be reflected upon, questioned and if necessary corrected, wherefore this study makes an important contribution to the discussion of cultural formation processes and their transformation into the archaeological record as well as bringing insights into the debate on context interpretation of material culture.